Dietary Supplementation of Curry (Murraya koenigii) Leaf Powder: Effects on Growth Performance, Nutrient Utilisation and Serum Biochemical Parameters in Crossbred Pigs - Bora, Mondira; Saikia, B.N.; Das, A.K.; Kalita, Dhireswar (Indian Journal of Animal Nutrition, 2018)
Eighteen Hampshire crossbred pigs (Av. BW= of 14.73 kg) irrespective of sex were randomly divided into 3 groups of 6 animals each and feeding trial continued for 80 days. The animals in all the three groups were fed grower ration (BIS, 1992) and curry leaves powder was included at 0, 0.5 and 1.0% level on DM intake basis in groups C, T1 and T2, respectively. The DM intake was similar in 3 groups. The highest average daily gain in body weight was found in group T2. The digestibility coefficient of DM, OM, EE, CF and NFE were similar in 3 groups, however, CP digestibility was better (P<0.05) in group T2 in comparison to groups C and T1. N retention was higher in group T2. Total serum protein level was higher (P<0.05) in group T2 followed by group T1. Serum glucose, serum cholesterol, AST, ALT levels were lower (P<0.05) in groups T2 and T1 than group C. The cost of production was lower (P<0.05) in group T2. Thus, supplementation of curry leaves powder @ 1% level showed better performance in respect of growth, prtotein utilization and economics of production.